Numerical investigation on the leaked nature gas diffusion of underground gas pipeline through soil to atmosphere. Issue 2 (July 2021) - Zhang, Tiantian; Qin, Yuxin; Han, Dongliang; Luo, Zonglin; Tan, Yufei
Abstract: When the buried gas pipeline leaks due to corrosion, aging, overload and other reasons, serious safety accidents are easy to occur. In this paper, a three-dimensional numerical model is established to simulate the underground gas diffusion from the directly buried pipeline, through the soil to the atmosphere. Using the model, the diffusion characteristics under the conditions of different initial pipeline pressures and different soil porosities are comparatively simulated and analysed. As indicated by the numerical results, when pinhole leakage occurs, the gas concentration exhibits a symmetrical distribution in the horizontal and axial directions. The gas content gradually reduces, as the distance from the leakage point increases. The diffusion process and gas content are largely determined by the initial leak pressure, as well as the flow resistance in accordance with the soil porosity.